How to make money marketing your business on YouTube - Turner, Jamie, 1961- ([FTPress], 2011)
Discover powerful, proven ways to use YouTube to attract new clients and customers! You've probably watched video on YouTube or other user-generated video sites such as HowCast, Flickr, or DailyMotion. But did you know you can make money using these platforms? It's not easy, but if you follow the path I'll outline, you'll find that user-generated video is a real, viable way to grow revenues and build your business.